Essential Issues Related to Construction Phases of Road Networks in Protected Areas: A Review - Sakar, Dursun; Aydin, Abdurrahim; Akay, Abdullah Emin (Zagreb Univ, Fac Forestry, 2022)
Protected areas play an active role in protecting natural resources and wildlife habitat. These areas must be accessible within protection-use balance. For this reason, road networks in protected areas are one of the main functions of sustainable infrastructure services. The construction phases of road networks in these sensitive areas should be considered in planning within the balance of protection-use with interdisciplinary studies. Especially during the construction of the road network, it is necessary to pay attention to the construction machinery used, geotextile materials, hydraulic and ecological road structures, plantation of the slopes, fences that increase the visual quality and work schedule. Based on a related literature survey, the issues to be considered during the construction phases of road networks (i.e. road planning, tree felling and removing, excavation and embankment, subgrade finishing, road structures and surfacing) in protected areas were evaluated under nine headings. The implementation phases of these issues are important in reducing the adverse effects that will occur in protected areas. In this regard, during the construction phases of road networks, the issues to be considered were evaluated together with the conceptual indicators in terms of management, technique, economy, ecology, and aesthetics. Matters needing attention according to the sensitivity of conceptual indicators during the construction phases of road networks in and around protected areas that contain sensitive ecosystems have been identified and presented in a framework to further the discussions on this issue. Accordingly, the use of the issues to be considered in the planning and construction of road networks with conceptual indicators will help evaluate the planning phase before and after construction. In particular, it can be expected to lead to the creation of a checklist after the planning phase. Thus, the continuity of the issues to be considered during the maintenance, repair, and construction phases of the new road networks or existing road networks planned to be built in a protected area and surrounding areas will provide significant contributions to the functions of the protected areas. The main contributions may include increasing the number of visitors to the protected areas, reducing impacts on wildlife in protected areas by implementing innovative technologies, and developing alternative modes in tourism industry.
Keywords: protected areas; road networks; construction phases; conceptual indicators